2015
DOI: 10.31018/jans.v7i2.664
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of antibacterial activity of two different earthworm species, Perionyx excavatus and Pheretima posthuma against pathogenic bacteria

Abstract: Disease outbreaks are being increasingly recognized as a significant constraint on aquaculture production and trade affecting the economic development of the sector in many countries. Extracting and using biologically active compounds from earthworms has traditionally been practiced by indigenous people throughout the world. The aim of the present study was to shown antimicrobial activity through earthworm extract against fish bacterial pathogens. In total, 8 bacterial strains i.e. 6 gram negative viz. Aeromon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
2
3
0
Order By: Relevance
“…Earthworms are terrestrial, important soil-dwelling organisms and considered ecosystem engineers [ 68 ]. The results of the current study prove that extract of various earthworm species can inhibit bacterial growth and have potent antioxidant and anticoagulant effects, and our results are consistent with the outcomes of Bansal et al [ 69 ] and Bansal et al [ 70 ].…”
Section: Discussionsupporting
confidence: 92%
“…Earthworms are terrestrial, important soil-dwelling organisms and considered ecosystem engineers [ 68 ]. The results of the current study prove that extract of various earthworm species can inhibit bacterial growth and have potent antioxidant and anticoagulant effects, and our results are consistent with the outcomes of Bansal et al [ 69 ] and Bansal et al [ 70 ].…”
Section: Discussionsupporting
confidence: 92%
“…Our next step was to determine the antibacterial potential of PCF and PBP, it was observed that three Gram positive (B. cereus, S. pyogenes and B. pumilus) and two Gram negative (P. putida and N. gonorrhoeae) showed sensitivity for PCF (100 µl/disc) while S. aureus, P. aeruginosa (Gram positive) and E. coli (Gram negative) were found resistant. Similarly, the findings of Vasanthi et al (2013) and Bansal et al (2015) support the results of sensitivity but regret the resistant behavior of S. aureus, P. aeruginosa and E. coli. The current results of PBP (100 µl/disc) antibacterial potential was much better than PCF because only one bacterial strain (P. aeruginosa) was resistant while all other were appeared either sensitive or intermediate.…”
Section: Discussionsupporting
confidence: 60%
“…Soil aggregate stability and plant growth were also positively affected by earthworm activities such as burrowing, mixing, and casting as in the case of M. guillelmi (Yu et al 2008). In addition, M. posthuma was also reported to bioprocess toxic compounds (Das et al 2015) and its extracts and casts exhibited antimicrobial activity (Kumar et al 2012;Bansal et al 2015). Casts of M. tschiliensis tschiliensis were also characterized to have higher nutrient content associated with higher gut microbial composition (Teng et al 2012).…”
Section: Discussionmentioning
confidence: 99%